-3(4+6w)-4=

Simple and best practice solution for -3(4+6w)-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4+6w)-4= equation:


Simplifying
-3(4 + 6w) + -4 = 0
(4 * -3 + 6w * -3) + -4 = 0
(-12 + -18w) + -4 = 0

Reorder the terms:
-12 + -4 + -18w = 0

Combine like terms: -12 + -4 = -16
-16 + -18w = 0

Solving
-16 + -18w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + -18w = 0 + 16

Combine like terms: -16 + 16 = 0
0 + -18w = 0 + 16
-18w = 0 + 16

Combine like terms: 0 + 16 = 16
-18w = 16

Divide each side by '-18'.
w = -0.8888888889

Simplifying
w = -0.8888888889

See similar equations:

| -18-10x=-16x+18 | | 189-10x=3x+20 | | 3v+30=6(v+8) | | 19v+7=167-v | | 3(-9-x)=42 | | 5000=0.3x^4-7.2x^3+43.2x^2+131.2 | | 6x+5+3x-1= | | 7k+12=19k-12 | | 4x+2y=190 | | 3(-9+x)=-21 | | x/5=60/75 | | 3[6+2(4+2)-5]+4= | | -7(5x+2)=-84 | | 5(-9+5q)= | | 2(2+5x)=-106 | | 6x^2+20-7x=0 | | 7(3x+1)-2(2x+4)= | | 7(2x+6)=-84 | | -2(6-4x)=44 | | u/3-13=1 | | -7(-7-x)=35 | | Log(X)=120 | | y=-25x+25 | | -4(2+5x)=152 | | 7.29x+21.87=43.74 | | (8x-7)(3-x)=0 | | 24x-20+21-30x=15 | | 2(-5-6x)=-46 | | 7b+-15=5b+-3 | | 11-2*3/5=0 | | -8(u-1)=-4u+12 | | 6x+24x-9=6(5x+5) |

Equations solver categories